Human herpesvirus 6 infection after autologous stem cell transplantation: A multicenter prospective study in adult patients. Issue 1 (July 2019) - Balsat, Marie; Pillet, Sylvie; Tavernier, Emmanuelle; Cacheux, Victoria; Escuret, Vanessa; Moluçon-Chabrot, Cécile; Augeul-Meunier, Karine; Mirand, Audrey; Regagnon, Christel; Tinquaut, Fabien; Bousser, Véronique; Oriol, Mathieu; et al.
Highlights: Active HHV-6 infection occurred in 11.2% of autologous stem cell recipients. HHV-6 infection is associated with delayed neutrophils and platelets recoveries. HHV-6 infection is associated to increased frequency of non-infectious complications. Non-infectious complications are more severe when associated to HHV-6 infection. Summary: Objectives: to prospectively evaluate the incidence and the clinical relevance on hematopoietic reconstitution of HHV-6 infection in autologous hematopoietic stem cell transplantation (ASCT) recipients. Methods: HHV-6 DNA load was measured in whole blood specimens once during the 7 days before stem cell re-infusion and once a week after transplantation until hematopoietic recovery. Active HHV-6 infection was defined by 2 consecutive positive DNA loads. Results: from July 2012 to February 2015, 196 adult patients undergoing ASCT were enrolled. Twenty-two (11.2%) patients developed active HHV-6 infection with a cumulative incidence of 19% at 40 days after transplantation. The onset of active HHV-6 infection occurred with a median of 13 days after stem cell re-infusion. HHV-6 infection was associated with an increased frequency of non-infectious complications (OR = 5.05; 95%CI 1.78–14.32; P  < 0.001). Moreover, the severity of these non-infectious complications was higher in recipients exhibiting HHV-6 infection (OR = 4.62; 95%CI 1.32–16.2; p  < 0.01). Delayed neutrophils 10 (IQR: 8–14) vs 8 (IQR: 6–11) days and platelets recoveries 15 (IQR: 11.8–18.5) vs 8 (IQR: 4–14) days were observed in patients with active HHV-6 infection compared to non-infected ones. Conclusions: in this study, 11.2% ASCT recipients presented active HHV-6 infection associated with significantly delayed hematologic reconstitution.